A randomized, blinded, prospective clinical trial of postoperative rehabilitation in dogs after surgical decompression of acute thoracolumbar intervertebral disc herniation. (10th April 2018) - Zidan, Natalia; Sims, Cory; Fenn, Joe; Williams, Kim; Griffith, Emily; Early, Peter J.; Mariani, Chris L.; Munana, Karen R.; Guevar, Julien; Olby, Natasha J.
Abstract : Background: Experimental evidence shows benefit of rehabilitation after spinal cord injury (SCI) but there are limited objective data on the effect of rehabilitation on recovery of dogs after surgery for acute thoracolumbar intervertebral disc herniations (TL‐IVDH). Objective: Compare the effect of basic and intensive post‐operative rehabilitation programs on recovery of locomotion in dogs with acute TL‐IVDH in a randomized, blinded, prospective clinical trial. Animals: Thirty non‐ambulatory paraparetic or paraplegic (with pain perception) dogs after decompressive surgery for TL‐IVDH. Methods: Blinded, prospective clinical trial. Dogs were randomized (1:1) to a basic or intensive 14‐day in‐house rehabilitation protocol. Fourteen‐day open field gait score (OFS) and coordination (regulatory index, RI) were primary outcomes. Secondary measures of gait, post‐operative pain, and weight were compared at 14 and 42 days. Results: Of 50 dogs assessed, 32 met inclusion criteria and 30 completed the protocol. There were no adverse events associated with rehabilitation. Median time to walking was 7.5 (2 – 37) days. Mean change in OFS by day 14 was 6.13 (confidence intervals: 4.88, 7.39, basic) versus 5.73 (4.94, 6.53, intensive) representing a treatment effect of −0.4 (−1.82, 1.02) which was not significant, P =.57. RI on day 14 was 55.13 (36.88, 73.38, basic) versus 51.65 (30.98, 72.33, intensive), a non‐significant treatment effect of −3.47 (−29.81, 22.87), P = .79. There were no differences in secondary outcomes between groups. Conclusions: Early postoperative rehabilitation after surgery for TL‐IVDH is safe but doesn't improve rate or level of recovery in dogs with incomplete SCI.